ANALISIS KEBERHASILAN PROGRAM SIKOMANDAN DALAM UPAYA MENINGKATKAN PENDAPATAN PETERNAK SAPI PERAH DI KOTA BATU - Wahyuning Islami; Nur Ida Iriani; Sumarno Sumarno; Cakti Indra Gunawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
It knows the success rate of Artificial Insemination (IB) for dairy cattle and of the SIKOMANDAN program on the income of dairy farmers based on birth date in Batu City and Knowing the factors that support the success of the SIKOMANDAN program in Batu City. The research was conducted using quantitative descriptive research and data collection was obtained through interviews with cow’s breeders and supporting literature. Using descriptive analysis and mathematical calculations. The artificial isemination program (IB) and SIKOMANDAN in Batu City is considered quite successful and satisfying because the program runs according to the expectations of the cows breeders. The factors that support the program include the support of human resources, paramedics, satisfactory service and support from the government. The existence of the SIKOMANDAN program is not only based on dairy cow’s, but also on other commodities such as beef cow’s and other livestock.